Effects of floods on crop farming: a case study of Budalangi Division, Kenya - Huho, Julius M.; Ang’awa, Francis Okere (International Journal for Disaster Management & Risk Reduction, 2008)
Floods are extreme weather events that occur when water rises to overflow on land that is not normally submerged. Flood is one the major natural disasters affecting man and his environment in Kenya, floods have been declared a National disaster. Budalangi Division, which lies in the floodplains of rivers Nzoia and Yala experiences floods every year. This has resulted in decline in agricultural production. The inhabitants of the division are threatened by food Insecurity and high poverty levels because of cumulative effects of floods. This paper examines the how floods affect crop farming in Budalangi Division of Busia district, Kenya.